ADAPTABILITY OF UV IRRADIATED MUTANT OF TRICHODERMA HARZIANUM TO CARBENDAZIM - A. A WALUNJ; PRIYA JOHN (The Bioscan, 2015)
Trichoderma harzianum, a potential bioagent used against different seed and soil borne plant pathogens is highly susceptible to the most widely used fungicide carbendazim. UV irradiated mutants of T. harzianum was developed by exposing T. harzianum to 30 W UV-irradiation for 10, 20, 30, and 40 min at 20 cm distance. Different concentrations of carbendazim (10, 20, 30, 50, 100 ìg/ml) were tested for sensitivity against wild and mutants of T. harzianum (Th-W, Th-M-1, Th-M-2, Th-M-3, Th-M-4). Mutant of T. harzianum Th-M-2 and Th-M-3 showed minimum growth inhibition at 10 ìg/ml concentration of carbendazim. Mutants T. harzianum (M-1, M-2, M-3, M-4) showed better inhibition as compared to wild T. harzianum (Th-W) at any concentration of the fungicide carbendazim.